Traços da ironia romântica n’A Estátua Amazônica, de Manuel de Araújo Porto-Alegre - Silva, Simone Aparecida da (2016)
A Estátua Amazônica (The Amazon Statue) is a comedy by Manuel de Araújo Porto Alegre, published in 1851. This work became the object through which the author has expressed his irony before some social segments of the time. Among the ironized targets in the text, one is part of the scientific academy of the nineteenth century, presenting as main argument the falsehood of a statue found on the shores of the Amazon River by foreign travelers who exhibited it in Paris. The aim of the present research was to analyze the linguistic resources used by the author to develop the romantic irony that circulates in the scene, resources that are manifested, especially, through the discourse of its protagonist characters. It also aimed to identify in the Porto Alegre’s work the romantic traits which distinguish it as a representative period of transition of: the trends and influences from European classicism in Brazilian literature to Romanticism which developed in Brazil.